George Orwell's Animal farm : the graphic novel - Orwell, George, 1903-1950; Dumalasova, Christina; Horakova, Katerina (Gemini Gift Books, 2026)
"All animals are equal, but some animals are more equal than others." When the downtrodden animals of Manor Farm overthrow their master Mr Jones and take over the farm themselves, they imagine it is the beginning of a life of freedom and equality. But gradually a cunning, ruthless elite among them - masterminded by the pigs Napoleon and Snowball - starts to take control. Soon the other animals discover that they are not all as equal as they thought and find themselves hopelessly ensnared as one form of tyranny is replaced with another. Orwell's chilling "fairy story" is a timeless and devastating satire of idealism betrayed by power and corruption. This powerfully and beautifully drawn graphic novel adaptation is destined to become the classic illustrated edition of this celebrated work."--